Autogenic training is an essential component in the rehabilitation of stuttering children - Utbasarova Umida (Zien Journals, 2022)
the article discusses the features of functional autogenic training with children suffering from stuttering at different stages of the rehabilitation course.
Keywords: stuttering; autogenic training; stutterers; phobia